Symptomatic treatment of effusions malignant of the serous - Badano Repetto, José Luis; Badano Carbajal, José Luis (Cirugía del Uruguay, 1973)
The authors refer their experience in symptomatic treatment of malign discharge of serosas. In 1953 they performed a derivation (shunt) through a skin tube, communicating the peritoneum with the cell tissue (subcutaneous tissue). La ter this tube was substituted by vinyl polichloride tubes. Their technique is simple applicable not only in the peritoneal but also in the pleural cavity. They believe that the. liquid probably has inmunological effect which yould add to the positive mechanical effect. Liquid is also extracted by the venous path. In both casse the_ patients are spared spoiiation resulting from repeated punctures. This method may also be applied in certain cases of peritoneal effusion due to portal hypertension.